Examination of workload perception, burnout, and perceived organizational support in emergency healthcare professionals: A structural equation model - Doğan, Aysun; Ertuğrul, Bekir; Akin, Kutay (Nursing & health sciences, 2024)
Job stress is one of the important factors affecting employee behavior. One of the most important factors in reducing burnout caused by stress is organizational support. In this context, the aim of this study is to identify the moderating role of perceived organizational support in the effect of workload perception on burnout within the emergency healthcare professionals’ universe. The data for this study were collected from 703 health professionals working in emergency health services in three major cities of Turkey. The relationships and the model of the study is analyzed by the Structural Equation Model technique. The results indicate that perceived workload is a factor that causes employee burnout, and perceived organizational support is a factor that reduces employee burnout. This study contributes to researchers and health managers by revealing the importance of workload planning and organizational activities that support employees to reduce burnout in health workers.